Virtual education, sustainable leadership, and social transformation: A university training experience with communities in Colombia - Naranjo Calderón, Camilo Ernesto (Journal of Education For Sustainable Innovation, 2025)
This article evaluates the impact of the Sustainable Leaders in Action project, developed by Uniminuto Virtual in Colombia through its Social Responsibility course, on transforming environmental attitudes and practices within local communities. The project led to a meaningful shift from theoretical understanding to applied sustainability, as participants began adopting behaviors such as recycling, organizing clean-up campaigns, and responsible water use. These changes reflected not only deeper environmental awareness but also the development of digital competencies for community engagement. Furthermore, the initiative fostered youth leadership, strengthened collaboration with local authorities, and promoted values of social justice and civic responsibility. Participants transitioned from passive recipients to active change agents, driving the replication of sustainability efforts in broader contexts. The findings highlight the project’s potential as a scalable model for environmental education and community empowerment.